Corticosterone potentiates ochratoxin A-induced microglial activation - Chansawhang A. (2023)
Microglial activation in the central nervous system (CNS) has been associated with brain damage and neurodegenerative disorders. Ochratoxin A (OTA) is a mycotoxin that occurs naturally in food and feed and has been associated with neurotoxicity, while corticosteroids are CNS' physiological function modulators. This study examined how OTA affected microglia activation and how corticosteroids influenced microglial neuroinflammation. Murine microglial cells (BV-2) were stimulated by OTA, and the potentiation effects on OTA-induced inflammation were determined by corticosterone pre-treatment. Expressions of pro-inflammatory mediators including tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), and inducible nitric oxide synthase (iNOS) were determined. Phosphorylation of mitogen-activated protein kinases (MAPKs) was analyzed by western blotting. OTA significantly increased the mRNA expression of IL-6, TNF-α, IL-1β, and iNOS and also elevated IL-6 and NO levels. Corticosterone pre-treatment enhanced the neuroinflammatory response to OTA in a mineralocorticoid receptor (MR)-dependent mechanism, which is associated with increases in extracellular signal-regulated kinase (ERK) and p38 MAPK activation. In response to OTA, microglial cells produced pro-inflammatory cytokines and NO, while corticosterone increased OTA-induced ERK and p38 MAPK phosphorylation via MR. Findings indicated the direct role of OTA in microglia activation and neuroinflammatory response and suggested that low corticosterone concentrations in the brain exacerbated neurodegeneration.